Unusual pericuff leak around proseal-laryngeal mask airway corrected by clamping gastric drain port: A case report (Indian Journal of Case Reports, 2021)
ProSealTM-Laryngeal Mask Airway (PLMA) (Laryngeal Mask Company, Henley-on Thames, UK) is commonly used for securing the airway with an added advantage over classic LMA as its gastric drain tube allows the insertion of Ryle’s tube and suctioning of gastric contents. The ProSeal LMA is designed in such a way that it allows controlled mechanical ventilation. During controlled mechanical ventilation, air leaks can occur because of positive airway pressures. Air leaks from the gastric drain port are almost always due to the malposition of PLMA. Here, we report a case of air leak from gastric drain port despite correctly placed PLMA and its successful management without removing the device.